O Campus Universitário de Breves e o desenvolvimento local: uma abordagem a partir da formação do capital - BORGES, Leticia da Costa (Universidade Federal do Pará, 2019)
The purpose of this research is to address the contribution of the Federal University of Para / University Campus Breves, from the formation of human capital and the production of the Campus of knowledge from the viewpoint of local and regional development in Marajó Archipelago emphasizing the municipality of Breves. So investigm up new models of local and regional development by assessing the role performed by the Campus Breves University as one of the development vectors from the training and development of local human capital and the production of knowledge through teaching activities , research and extension. Therefore, the central objective outlined by the analytical description of the training, research and extension and the impact of those activities on the local and regional development / municipality of Breves. Thus, we propose the development of an information-based model to manage the process. The metológico procedure used was the bibliographical and documentary research by measurement (quantitative and qualitative) that impact on the development of the municipality of Breves / Region Marajó. The results point to significant contributions to the development of the region with regard to the sectors of education and health. Working with the proposition of a set of alternative strategies for local and regional development It is concluded